Topographic mapping of a specimen after endoscopic submucosal dissection - Ebigbo, Alanna; Probst, Andreas; Messmann, Helmut; Märkl, Bruno; Nam-Apostolopoulos, Yun-Chung (Endoscopy International Open, 2019)
Background and study aims Mapping of pathologic specimens after endoscopic submucosal dissection (ESD) is common practice in Asian countries, especially in Japan. However, there is a lack of awareness for this technique in Europe. In this report, we demonstrate the feasibility and benefits of topographic mapping in a Western setting.